2010
DOI: 10.1242/jcs.063172
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasted: a novel component of theDrosophilahistone locus body required for muscle integrity

Abstract: SummarySkeletal muscles arise by cellular differentiation and regulated gene expression. Terminal differentiation programmes such as muscle growth, extension and attachment to the epidermis, lead to maturation of the muscles. These events require changes in chromatin organization as genes are differentially regulated. Here, we identify and characterise muscle wasted (mute), a novel component of the Drosophila histone locus body (HLB). We demonstrate that a mutation in mute leads to severe loss of muscle mass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 67 publications
(92 reference statements)
1
64
0
Order By: Relevance
“…The homology, although very limited, also extends to the C-terminal regions (Fig. 7A) (28). In contrast, no obvious sequence similarity can be observed between the C-terminal regions of NPAT and Mxc (data not shown).…”
Section: Overexpression Of the C-terminal Regions Of Flash Or Npat Rementioning
confidence: 90%
See 4 more Smart Citations
“…The homology, although very limited, also extends to the C-terminal regions (Fig. 7A) (28). In contrast, no obvious sequence similarity can be observed between the C-terminal regions of NPAT and Mxc (data not shown).…”
Section: Overexpression Of the C-terminal Regions Of Flash Or Npat Rementioning
confidence: 90%
“…Studies on YARP suggested that it functions as a transcriptional regulator involved in controlling critical developmental decisions but provided no information on the role of its C-terminal domain (49,58). YARP is a homologue of Drosophila Mute, a protein of unknown function shown to localize to HLBs in Drosophila cells and embryos (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations